2002
DOI: 10.2486/indhealth.40.59
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Hand-Arm Vibration Syndrome in Okinawa, a Subtropical Area of Japan.

Abstract: The purpose of this study was to understand the peculiarity of the development of HandArm Vibration Syndrome (HAVS) in a subtropical area of Japan. We analyzed the medical records of 21 subjects reported by the Okinawa Labor Bureau, and tried to determine whether the warm environment has any effect on the severity of HAVS. The mean operating time of vibration tools for all the subjects was over 10,000 hrs. Almost all the subjects from Okinawa had been working only in Okinawa. The presence of Vibration Induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 8 publications
(8 reference statements)
3
15
0
Order By: Relevance
“…There is a huge gap between this study and both previous studies in terms of job duration. This finding is similar with that reported in Vietnam, Papua New Guinea and Indonesia, which concluded that factors of climate (more than 25°C), young workers and shorter work experience play important roles in reducing the vibrating effect 12,13,[23][24][25] . The final factors in this study was the climate condition 12,13,[23][24][25] .…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…There is a huge gap between this study and both previous studies in terms of job duration. This finding is similar with that reported in Vietnam, Papua New Guinea and Indonesia, which concluded that factors of climate (more than 25°C), young workers and shorter work experience play important roles in reducing the vibrating effect 12,13,[23][24][25] . The final factors in this study was the climate condition 12,13,[23][24][25] .…”
Section: Resultssupporting
confidence: 81%
“…(62%), Lindsell 22) (98%). However, the prevalence of HAVS in this study was still high compared to the prevalence of the normal population 12,13,[23][24][25] . The prevalence of tingling or numbness in fingers among an unexposed male population is 11.9% 26) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our study support the hypothesis that low outdoor temperatures increase the prevalence of selfreported WF among workers exposed to HAV, which is in agreement with earlier studies (1,(3)(4)(5). The average annual temperature was about 0º C in the northern region compared to 8º C in the southern region during the actual time period (9).…”
Section: Discussionsupporting
confidence: 82%
“…Studies of HAV-exposed workers in tropical or subtropical areas have shown no, or very small prevalence of WF (2)(3)(4) leading the authors to conclude that the absence of symptoms could be due to the warm climate. A study carried by Yu et al (5) is the only one, as far as we know, where workers in both cold and warm climate have been studied on the same occasion.…”
mentioning
confidence: 98%